2011
DOI: 10.1007/s00535-011-0438-2
|View full text |Cite
|
Sign up to set email alerts
|

Daikenchuto (TU-100) ameliorates colon microvascular dysfunction via endogenous adrenomedullin in Crohn’s disease rat model

Abstract: In the ischemic colon, endogenous βCGRP, but not ADM, was decreased. Thus, it was concluded that TU-100 ameliorated microvascular dysfunction by the up-regulation of endogenous ADM in the CD rat model. TU-100 may be a possible therapeutic agent for gastrointestinal ischemia-related diseases including CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
2
64
0
1
Order By: Relevance
“…After therapy with daikenchuto, abdominal gas volume assessed by radiographic examination was significantly reduced. Daikenchuto treats abdominal symptoms by enhancing the secretions of motilin (Nagano et al, 1999), substance P (Kono et al, 2008), calcitonin gene-related peptide, and adrenomedullin (Kono et al, 2010(Kono et al, , 2011, and activating the transient receptor potential vanilloid (Kikuchi et al, 2013). Keishikashakuyakuto is also used to treat functional abdominal pain, and the effects on irritable bowel syndrome have been investigated in a double blind RCT (Sasaki et al, 1998).…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…After therapy with daikenchuto, abdominal gas volume assessed by radiographic examination was significantly reduced. Daikenchuto treats abdominal symptoms by enhancing the secretions of motilin (Nagano et al, 1999), substance P (Kono et al, 2008), calcitonin gene-related peptide, and adrenomedullin (Kono et al, 2010(Kono et al, , 2011, and activating the transient receptor potential vanilloid (Kikuchi et al, 2013). Keishikashakuyakuto is also used to treat functional abdominal pain, and the effects on irritable bowel syndrome have been investigated in a double blind RCT (Sasaki et al, 1998).…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…Jejunal blood flow was measured by a laser-Doppler flowmeter (ALF21N, Advance, Tokyo) as previously described (30). Briefly, rats were anesthetized with urethane (900 mg/kg ip), ␣-chloralose (45 mg/kg ip), and butorphanol (1 mg/kg im).…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have shown that TU-100 increases blood flow in the small intestine of normal rats (38) and potentiates the production of vasoactive ADM by IE cells (27,30). Accordingly, we sought to identify the TRP channel involved in the vasodilatory effect of TU-100.…”
Section: Upregulation Of Ibf By Trpv1 and Trpa1 Stimulationmentioning
confidence: 99%
“…Further, recent studies have addressed the possibility that DKT increases intestinal blood flow and ameliorates colitis via calcitonin gene-related peptide or adrenomedullin (Murata et al, 2002;Kono et al, 2008Kono et al, , 2010Kono et al, , 2011. The wide range of medicinal actions of DKT has been attributed to its multiple active constituents such as sanshools, shogaols, and ginsenosides.…”
Section: Introductionmentioning
confidence: 99%